EFEKTIVITAS KONSELING KOGNITIF-PERILAKU DENGAN TEKNIK LATIHAN ASERTIF UNTUK MENGATASI TINDAKAN KEKERASAN PADA ANAK - Mubiar Agustin; Ipah Saripah; Asep Deni Gustiana (Jurnal Ilmiah Visi, 2016)
This research is based on the most fundamental problem in teaching young learners, especially in preschool, which is the tendency of the children’s behavior within each other in the learning process that leads to abuse. One of the offered solutions to address abuse is to provide preventive act through Cognitive-Behavior Counselling activities with Assertive Training Technique. The aim of this research is to conduct cognitive-behavior counselling activities with assertive training technique in way that is correct, tested and comprehensive to address child abuse. The research was conducted by applying quasi experimental method in the year of. 2015 – 2016 in Bandung District. The subject of the research was group B students of Al Muqoddasah Preschool Bandung District. The result shows that: (1) the forms of child abuse consist of physical, verbal and relational abuse; (2) cognitive-behavior counselling activities with assertive training technique to address abuse are considered appropriate to implement by experts; and (3) there is a significant impact of cognitive-behavior counselling activities in minimize child abuse.